Screening diabetické makulopatie - Kalvodová, B; Oudová, P (Ceska a slovenska oftalmologie, 2002)
Diabetic maculopathy (DMP) is an important but curable of eyesight losses in diabetic with type 1 and 2 diabetic mellitus (DM). In the submitted work the author investigates the pathogenesis of diabetic macular oedema (DME). Classification, diagnosis and standard of treatment of DMP, incl. the different therapeutic procedure used in concurrent DMP and proliferative diabetic retinopathy in DM type 1 and 2.
Keywords: lidé; Diabetic Retinopathy; Humans; macula lutea; Macula Lutea; diabetická retinopatie